A fundamental study on biological removal of N2O in the presence of oxygen. (September 2016) - Figueroa-González, Ivonne; Quijano, Guillermo; Laguna, Inés; Muñoz, Raúl; García-Encina, Pedro A.
Abstract: The biodegradation of N2 O by a non-acclimated secondary activated sludge in the presence of O2 was studied. Batch tests with a headspace containing an initial N2 O concentration of ∼400 mg m −3 (∼200 ppmv ) and initial O2 gas concentrations of 0%, 1%, 2%, 5% and 21% were investigated. The effect of O2 on the biokinetic parameters qmax (maximum specific N2 O uptake rate) and KS (half-saturation constant), as well as on the bacterial population structure, was evaluated. A complete N2 O removal was recorded in the presence of up to 2% O2, while O2 at 5% and 21% mediated inhibitions of 37% and 95% in the removal of N2 O compared with the control without O2 . The elemental analysis of the biomass obtained at the end of the batch tests strongly suggested that NN2 O was not used as a nitrogen source. The presence of O2 mediated decreases of up to 12.6- and 4.8-fold in qmax and KS, respectively, compared to the control without O2 . Likewise, the presence of O2 induced changes in the structure of the bacterial population. The predominant microorganisms in the presence of O2 belonged to the phyla Proteobacteria, Firmicutes and Chlamydiae . Bacteria belonging to the Proteobacteria phylum, particularly the Dokdonella genus, were predominant at 2% O2, which was the highest O2 concentration without inhibitory effects on N2 O biodegradation. Graphical abstract: Highlights: N2 O was fully biodegraded in the presence of up to 2% O2 . N2 O removal inhibition was observed at O2 concentrations ≥5%. The presence of O2 mediated changes in the biokinetic parameters. O2 mediated uncompetitive inhibition for N2 O degradation. O2 produced significant changes in the N2 O-degrading bacterial population.